The presence of pain in community-dwelling South African manual wheelchair users with spinal cord injury - Mokgadi K. Mashola; Elzette Korkie; Diphale J. Mothabeng (AOSIS, 2022)
Background: Pain after spinal cord injury (SCI) is common and is likely to continue throughout life with varying levels of severity. Objective: To determine the presence of pain, the sociodemographic and injury profile of community-dwelling manual wheelchair users. Method: This quantitative correlational study used a sociodemographic and injury profile sheet and the Douleur Neuropathique 4 Questions (DN4) questionnaire to document demographic, SCI profiles as well as pain characteristics. Pain severity was determined using the Numeric Rating Scale. Data were analysed using the Statistical Package for the Social Sciences (SPSS) v27 at 0.05 level of significance. Results: The pain rate was 104; 85% of 122 participants and mainly in those with complete SCI (77.9%). Neuropathic pain was more common (76; 62.5%) and significantly associated (p 0.05) with higher pain severity. Pain was mainly in one area of the body (59; 48.4%) but occurring in up to five areas. The most painful area had a mean severity of 6.7/10; was more common in the lower limbs below the injury level (48; 39.4%); and was burning in nature (40; 32.7%). Conclusions: Pain after SCI is as problematic in the South African context as it is globally. With the rising SCI prevalence in the country, understanding pain and its presentation is important for holistic management of a person with SCI. Clinical implications: In-depth assessment of pain should be conducted and appropriate management interventions for specific pain types be prescribed to effectively reduce pain.